Biomechanical Regulation of Mesenchymal Stem Cells for Cardiovascular Tissue Engineering. Issue 22 (25th September 2017) - Henderson, Kayla; Sligar, Andrew D.; Le, Victoria P.; Lee, Jason; Baker, Aaron B.
Abstract: Mesenchymal stem cells (MSCs) are an appealing potential therapy for vascular diseases; however, many challenges remain in their clinical translation. While the use of biochemical, pharmacological, and substrate‐mediated treatments to condition MSCs has been subjected to intense investigation, there has been far less exploration of using these treatments in combination with applied mechanical force for conditioning MSCs toward vascular phenotypes. This review summarizes the current understanding of the use of applied mechanical forces to differentiate MSCs into vascular cells and enhance their therapeutic potential for cardiovascular disease. First recent work on the use of material‐based mechanical cues for differentiation of MSCs into vascular and cardiovascular phenotypes is examined. Then a summary of the studies using mechanical stretch or shear stress in combination with biochemical treatments to enhance vascular phenotypes in MSCs is presented. Abstract : Published work relating to the use of mechanical forces to condition mesenchymal stem cells into vascular phenotypes for therapeutic applications is examined in this review. The synergistic interactions of substrate compliance, nanopatterning, and biochemical treatments with applied mechanical stretch or fluidic shear stress on the vascular and cardiac differentiation of mesenchymal stem cells are examined.